The plant pixies - Pearl, Alexa, 1967-; Sordo, Paco (New York, NY : Little Bee Books, 2017)
Sasha learns what her special, royal power is when she tries to stop plant pixies from stealing feathers from the flying horses.
2.4
K-3
560L
Keywords: Horses -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Princesses -- Juvenile fiction; Pixies -- Juvenile fiction; Friendship -- Juvenile fiction; Horses -- Fiction; Animals, Mythical -- Fiction; Princesses -- Fiction; Pixies -- Fiction; Friendship -- Fiction